A Work in Progress : Integrating Markets for Goods, Labor, and Capital in the East African Community - Alper, Emre.; Chen, Wenjie; Dridi, Jemma; Joly, Herve (Washington, D.C. : International Monetary Fund, 2017)
This paper assesses the extent of economic and financial integration among the East African Community (EAC) along a number of dimensions and, where possible, whether integration has increased in the wake of the major regional integration policy milestones.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet